Clinical outcomes of arthroscopic pan-capsular release with or without entire coracohumeral ligament release for patients with frozen shoulder - Hagiwara, Yoshihiro (JSES Int, 2020)
BACKGROUND: We aimed to retrospectively determine the effects of arthroscopic pan-capsular release with or without entire coracohumeral ligament (CHL) release and diabetes mellitus (DM) in patients with frozen shoulder (FS). METHODS: The study included 34 patients (20 male and 14 female patients) who underwent arthroscopic pan-capsular release without entire CHL release (group 1) and 26 patients (6 male and 20 female patients) who underwent entire CHL release for FS (group 2). Patients with a minimum of 12 months of follow-up were included, and range of motion (ROM) and the shoulder rating scale of the University of California at Los Angeles (UCLA) scoring system were evaluated. RESULTS: In group 2, external rotation and hand-behind-the-back (HBB) ROMs were significantly increased compared with group 1 at the final follow-up (external rotation, 53.1° ± 15.2° vs. 41.3° ± 20.5° [P = .044]; HBB level, T6 [interquartile range, T5-T9] vs. T11 [interquartile range, T8-L4] [P < .001]). Total UCLA scores and UCLA scores for pain (9.2 ± 1.5 vs. 10.0, P = .003), function (8.5 ± 1.4 vs. 10.0, P < .001), and active forward flexion (4.6 ± 0.6 vs. 4.9 ± 0.2, P < .011) were significantly greater in group 2 at the final follow-up. Patients without DM tended to have greater recovery of forward flexion and HBB ROMs and better total, pain, and function UCLA scores compared with those with DM. In group 2, there were no significant differences in ROMs and UCLA scores between the patients with DM and those without DM. CONCLUSION: Arthroscopic entire CHL release is an essential treatment option for FS patients to regain ROMs and function and to reduce pain.